2006
DOI: 10.1562/2005-04-23-ra-496
|View full text |Cite
|
Sign up to set email alerts
|

Quinone-sensitized Steady-state Photolysis of Acetophenone Oximes Under Aerobic Conditions: Kinetics and Product Studies†

Abstract: Oxidation of oximes via photosensitized electron transfer (PET) results in the formation of the corresponding ketones as the major product via oxime radical cations and iminoxyl radicals. The influence of electron-releasing and electron-accepting substituents on these reactions was studied. The observed substituent effect strongly supports formation of iminoxyl radicals from the oximes via an electron transfer-proton transfer sequence rather than direct hydrogen atom abstraction. Correlation of the relative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…It is hypothesized that the adduct contained a gemcyanonitroso structure resulting from capture of a reactive oxime derivative by cyanide ion ( Figures 3 and 6). A proposed reaction mechanism involves further oxidation of the oxime to a putative nitroso carbocation which reacts with À CN to form the final product (Park et al 2006) (Figure 6). The oxime would be expected to exist in a tautomeric equilibrium with the corresponding nitroso species, several of which are known to form an metabolite intermediate complex with P450, leading to inactivation of the enzyme (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that the adduct contained a gemcyanonitroso structure resulting from capture of a reactive oxime derivative by cyanide ion ( Figures 3 and 6). A proposed reaction mechanism involves further oxidation of the oxime to a putative nitroso carbocation which reacts with À CN to form the final product (Park et al 2006) (Figure 6). The oxime would be expected to exist in a tautomeric equilibrium with the corresponding nitroso species, several of which are known to form an metabolite intermediate complex with P450, leading to inactivation of the enzyme (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Oxime-derived compounds have a broad range of applications such as industrial chemicals, pharmaceuticals, and antidotes for nerve gas poisoning. Because oximes and oxime ethers contain two heteroatoms, they are popular reagents for the synthesis of heterocycles, including natural products and pharmaceuticals via intermolecular and intramolecular reactions. We have previously reported on the use of 2′-arylbenzaldehyde oxime ethers as precursors for the synthesis of phenanthridine derivatives under photoinduced electron transfer (PET) conditions . This work was based on the observation that oxime ether radical cations underwent intermolecular nucleophilic attack at the nitrogen, whereas oximes did not show such reactivity but instead formed the corresponding carbonyl or nitrile via the proposed iminoxyl or iminoyl radicals. , The intermediate oxime radical cations are highly acidic and quickly lose a proton to form an iminoxyl radical, which might be more prone to react with a built-in radical trap. ,, Our initial study on the oxidative cyclization reactions of oximes and oxime ethers showed that built-in aromatic rings behaved as nucleophiles reacting with the nitrogen atom of the oxime ether moiety . Because the oximes did not show such reactivity, it was proposed that aromatic rings do not act as radical traps.…”
Section: Introductionmentioning
confidence: 99%
“…Given the differences that we observed between the metal-catalyzed cyclization reactions and the oxidative cyclization reactions of the 2′-arylbenzaldehyde oxime ethers under PET conditions, we set out to investigate the behavior of alkyne groups in a set of ortho -alkynyl benzaldehyde and acetophenone oximes and oxime ethers under PET conditions (see Figure ). Our recent work has shown that radical cation intermediates are easily generated when using oxime ethers and 9,10-dicyanoanthracene (DCA) as the sensitizer or with chloranil (CA) as the sensitizer. ,, However, previously, we have proposed that using CA as a sensitizer in the PET reactions of oximes results in the formation of iminoxyl radicals, presumably because the CA radical anion is a basic species and aids in the deprotonation of the oxime radical cation (as seen by formation of the semiquinone radical under those conditions) . Alternatively, because the DCA radical anion is not a strong base, using DCA as the photosensitizer could allow us to generate the oxime radical cations without facilitating the deprotonation step.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38] Furthermore, according to the proposed mechanism for the photooxidation of aldoximes that can yield the corresponding aldehyde and nitrile, the aldehyde/nitrile product ratio is largely determined by the relative stability of the iminoxyl radical as compared with the iminoyl radical. 31,39 Due to these reasons, it is important to acquire a sound knowledge about the O-H BDEs of various types of oximes. Unfortunately, during the past several decades, there have been some heated controversies over the experimental values of oxime O-H BDEs.…”
Section: Introductionmentioning
confidence: 99%